The Effects of Chitosan Organic Fertilizer and Urea Inorganic Fertilizer Application on the Growth of Pakcoy Mustard Plants (Brassica rapa L.) - Melati Putri Br Simanjuntak; Muhammad Idris (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the effects of inorganic urea fertilizer, organic chitosan fertilizer, and their interaction on the growth and yield of pakcoy mustard (Brassica rapa L.). The experiment used a factorial randomized block design (RBD) with two factors: urea fertilizer dose, consisting of U0 (0 g plant⁻¹), U1 (0.8 g plant⁻¹), U2 (1.2 g plant⁻¹), and U3 (1.6 g plant⁻¹), and chitosan concentration, consisting of K0 (0%), K1 (20%), K2 (30%), and K3 (40%). Each treatment combination was replicated three times. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT). The results showed that urea fertilizer significantly affected plant height, number of leaves, stem base diameter, fresh weight, and chlorophyll content. The best responses were generally obtained at 1.6 g plant⁻¹ urea, while stem base diameter and chlorophyll content showed optimal responses at 1.2 g plant⁻¹ and 0.8–1.2 g plant⁻¹, respectively. Chitosan application also significantly improved pakcoy growth, with the best overall response observed at 40%. The interaction between urea and chitosan significantly affected plant height, stem base diameter, and fresh weight. The U3K3 treatment produced the highest plant height from 1 to 4 weeks after transplanting, as well as the highest stem base diameter and fresh weight. Meanwhile, the highest number of leaves and chlorophyll content were obtained in U2K2. Overall, the combined application of urea and chitosan enhanced pakcoy growth and yield performance.